Are Faster Participants Always Faster? Assessing Reliability of Participants’ Mean Response Speed in Picture Naming - Fuhrmeister, Pamela; Elbuy, Shereen; Bürki, Audrey (Journal of cognition, 2024)
Studies of language production often make use of picture naming tasks to investigate the cognitive processes involved in speaking, and many of these studies report a wide range of individual variability in how long speakers need to prepare the name of a picture. It has been assumed that this variability can be linked to inter-individual differences in cognitive skills or abilities (e.g., attention or working memory); therefore, several studies have tried to explain variability in language production tasks by correlating production measures with scores on cognitive tests. This approach, however, relies on the assumption that participants are reliable over time in their picture naming speed (i.e., that faster speakers are consistently fast). The current study explicitly tested this assumption by asking participants to complete a simple picture naming task twice with one to two weeks in between sessions. In one experiment, we show that picture naming speed has excellent within-task reliability and good test-retest reliability, at least when participants perform the same task in both sessions. In a second experiment with slight task variations across sessions (a speeded and non-speeded picture naming task), we replicated the high split-half reliability and found moderate consistency over tasks. These findings are as predicted under the assumption that the speed of initiating responses for speech production is an intrinsic property or capacity of an individual. We additionally discuss the consequences of these results for the statistical power of correlational designs.